Rekonstruksi Pemikiran Syed Muhammad Naquib Al-Attas terhadap Pendidikan Islam di Tengah Dekadensi Moral Era Society 5.0 - Fitriani Fitriani; Hasan Basri; Andewi Suhartini (UIN Sunan Gunung Djati Bandung, 2023)
Islamic education has a crucial role in shaping the morality of students. This study aims to discuss Syed Muhammad Naquib al-Attas's thoughts on Islamic education amid the moral decadence of Era Society 5.0. This research uses a descriptive-analytical method with a qualitative approach. The conclusion of the study of the reconstruction of Syed Muhammad Naquib al-Attas's thoughts on Islamic education amid the moral decadence of the Era Society 5.0 is that ideally, Islamic education reflects the cultivation of khuluqi values and discipline of body and soul so that it has implications for improving the character and behavior of students. Some of the efforts that educators can make in building morals in students in the Era Society 5.0 are: 1) educators provide comprehensive and universal education to students; 2) educators introduce and instill good values; 3) accompany and show good things; 4) build cooperation between educators and parents in the process of instilling good values.